Dynamics of Culture and Social Organization of Five Ethnic Groups in the Archipelago: Comparative Analysis of the Communities of Gorontalo, Makassar, Papua, Flores, and Timor - Marzuti Isra; Rajwa Nur Aisyah Harahap; Muhammad Handika Sabil; Rizki Pariansyah Nasution; Rifki Azwar Sagala; Al Fahmi Nazril Buchori; Albert Jonathan Sigiro (Jurnal Multidisiplin Sahombu, 2025)
This study examines the cultural dynamics and social organization of five Indonesian ethnic groups Gorontalo, Makassar, Papua, Flores, and Timor—in response to modernization pressures. Using a qualitative comparative design with ethnographic approaches and literature review (2015–2025), distinct adaptation patterns are revealed. Gorontalo society contends with local language erosion and dualism of traditional authority but integrates Islamic values into rituals like Burdah. Makassar recontextualizes Siri’ Na Pacce for multiethnic urban interactions and institutionalizes Appassili through education. Papua experiences social fragmentation due to disparities in special autonomy policies and cultural commodification, with churches mediating conflicts. Flores harmonizes Catholicism with Caci rituals and Go'et Idep oral traditions, yet navigates sacred-meaning reduction from tourism. Meanwhile, Timor sustains identity via the Tetum language in diasporas but grapples with geopolitical fragmentation post-1999. Commonalities lie in kinship-based social structures as cultural anchors, while differences emerge in adaptation strategies: institutionalization (Gorontalo-Makassar), hybridization (Papua-Flores), and cross-border identity (Timor). The research enriches cultural complexity theory (Hannerz) and recommends gradient protection policies for cultural preservation.